Tax Avoidance by Reputable Companies: Does Brand Value Have Moderating Role? - Debby Prima Andriawan; Roekhudin; Syaiful Iqbal (Universitas Muhammadiyah Malang, 2024)
Purpose: To examine the effect of profitability and capital intensity on tax avoidance and to determine the role of brand value in moderating the effect of profitability and capital intensity on tax avoidance. Methodology/approach: Using a purposive sampling method, producing 190 observation data from 75 companies listed on the Indonesia Stock Exchange and included in the top 100 strongest and most valuable brands published by Brand Finance in 2017 to 2019. The relationship between variables will be tested using data panel regression analysis with moderation effects (Moderation Regression Analysis). Findings: Profitability has a positive effect on tax avoidance, while capital intensity has a negative effect on tax avoidance. Furthermore, the moderating role of brand value was found in the effect of profitability on tax avoidance, but not found in the effect of capital intensity on tax avoidance. Practical implications: When companies avoid taxes, they not only take into account their profitability but also consider their brand value. High brand value shows that the company has a good reputation, and in essence the company will try to maintain its good reputation by not avoiding taxes. Originality/value: Provides empirical evidence on the moderating role brand value on the effect of profitability and capital intensity on tax avoidance.